1997
DOI: 10.1111/j.1432-1033.1997.t01-2-00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor Y Controls the Basal Transcription Activity of the Mouse Platelet‐Derived‐Growth‐Factor β‐Receptor Gene

Abstract: To determine the regulatory mechanism of the expression of the mouse platelet-derived growth factor (PDGF) p-receptor gene, a 1.9-kb 5' flanking genomic fragment was cloned and analyzed. Site

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…In fact, the overexpression of p73␣ yielded a comparable repression as was seen by DNNF-YA alone on the promoter. These results indicate that p73␣ represses the promoter activity by its effect on NF-Y, attenuating the stimulatory effect of NF-Y on the promoter (14).…”
Section: Repression Of Pdgf ␤-Receptormentioning
confidence: 73%
See 2 more Smart Citations
“…In fact, the overexpression of p73␣ yielded a comparable repression as was seen by DNNF-YA alone on the promoter. These results indicate that p73␣ represses the promoter activity by its effect on NF-Y, attenuating the stimulatory effect of NF-Y on the promoter (14).…”
Section: Repression Of Pdgf ␤-Receptormentioning
confidence: 73%
“…Complex to the PDGF ␤-Receptor Promoter-To examine whether NF-Y complex binding to DNA changes during cell cycle, electrophoresis mobility shift assay was performed with a 32 P-labeled double-stranded oligonucleotide probe for PDGF ␤-receptor promoter containing the CCAAT motif (14). Nuclear protein was taken at various time points after serum stimulation from NIH3T3 cells that had been kept in a serum-free medium for 48 h. As shown in Fig.…”
Section: Serum Stimulation Decreases Binding Of Endogenous Nf-ymentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence analysis of the minimal promoter region revealed a TATA-less promoter with consensus binding sites for known transcription factors including Sp1, GATA, CREB and NF-1. Funa and colleagues, who cloned the PDGF-betaR gene independently, have suggested that a single NF-Y site 60 bp upstream of the transcriptional start site is critical for basal promoter activity (80). Studies are currently underway in our laboratory to identify the putative cisacting elements and trans-acting factors that mediate regulated changes in PDGF-R expression.…”
Section: Transcriptional Regulation Of Pdgf-betar Expressionmentioning
confidence: 99%
“…The expression levels of all the constructs were examined and the expression of LT in two different vectors was judged to be similar by immunoblotting 3T3 cell lysates after transfection. For functional promoter assays, the promoter region of mouse PDGF β-receptor was inserted in a luciferase expression vector, pGL3 (Promega) (Ishisaki et al, 1997). The dominant negative mouse NF-YA (DNNFYA) was provided by Dr Mantovani (Mantovani et al, 1994), and Sp1 cDNA was provided by Dr Tjian (Howard Hugh Medical Institute, University of California, CA).…”
Section: Plasmid Constructsmentioning
confidence: 99%